Review article: The Effect of Exercise On Fat Browning through Plasma Irisin Level Modulation to Overcome Obesity - Amaliyah, Miftahul Nur; Rejeki, Purwo Sri (Folia Medica Indonesiana, 2018)
Overweight and obesity incidence continues to increase and becomes a global problem in recent decades. One of the pathophysiology is a low energy output, therefore energy homeostasis shifts positively. Exercise is considered as an effective method to increase energy output. Irisin is one of myokine type that is secreted to the bloodstream while exercising and causes changes in subcutaneous adipose tissue. In adipose cells, irisin will stimulate the browning process in White Adipose Tissue to increase thermogenesis and lipolysis.